Do real exchange rates contain a unit root? Evidence from Turkish data - Tastan, H (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2005)
This study explores whether the long-run purchasing power parity (PPP) hypothesis holds for selected real exchange rates from Turkish economy during the period 1982M 1-2003M 12. In addition to conventional unit root tests, five different unit root test procedures have been applied including efficient point-optimal tests, extended M tests and GLS-detrended variants of DF tests, to four monthly real exchange rate series defined in terms of both producer and consumer price indices. The countries analysed are the USA, the UK, Germany and Italy which are major trade partners of Turkey. Mixed evidence is found for the long-run PPP hypothesis when real exchange rate is defined in terms of German DM and Italian Lira. However, the empirical analysis reveals that the PPP hypothesis holds strongly in the long-run for the UKE and US$ based real exchange rates series using either PPI or CPI. In corroboration with other studies in the literature, the bias correlated half-life estimates suggest relatively faster speeds of adjustment supporting the view that the deviations from the PPP rate dissipate rather quickly for relatively high inflation countries.
Keywords: PURCHASING POWER PARITY; AUTOREGRESSIVE TIME-SERIES; HIGH INFLATION COUNTRY; NULL HYPOTHESIS; RATE BEHAVIOR; PANEL; STATIONARITY; TESTS; PPP; PERSISTENCE; Business & Economics